Analisis Berbagai Macam Biomarker Air Mata dalam Diagnosis Penyakit Mata Kering - Muhammad Furqan; Sukma Purnama Sidhi; Lulu Chotim Amsari (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2020)
Introduction: The diagnosis of dry eye disease (DED) especially in the early stages is important, but difficult. This is due to the lack of a gold standard and a poor correlation between the biochemical changes in tears and clinical signs. Tear biomarkers can be used in diagnosing and monitoring DED because they are non-invasive, and have a good correlation with biochemical changes in tears and disease progression. Purpose: This article will describe some of the most important tear biomarkers for DED, namely markers for lacrimal gland dysfunction, inflammation, oxidative stress, and contact lens intolerance, and its correlation with subtypes and disease severity. Method: The method used is literature study using the last 10 years journals obtained from search engines such as Sciencedirect, PubMed, Google Scholar and ClinicalKey. Discussion: Biomarkers for lacrimal gland dysfunction are characterized by changes in protein levels (lactoferrin, lysozyme, etc.), neuromediators (NGF, CGRP, NPY, Serotonin), and mucin ((MUC)5AC); while the inflammatory response is characterized by changes in the expression of cytokines, chemokines, MMP-9, and albumin. Oxidative stress is characterized by changes in lipid levels (HNE, MDA). Meanwhile contact lens intolerance is associated with changes in 1D1-secretoglobin, ?2-microglobulin, lacritin, secretoglobin 1A2, albumin, LPRR4, LCN-1, and PIP. Conclusion: MMP-9 and a combination of Mammaglobin-B, lipophilin-A, and B2MG are biomarkers with the highest sensitivity and specificity of other biomarkers. Some of these biomarkers can be used to diagnose DED, differentiate between Sjögren DED syndrome and non-Sjögren DED syndrome, ADDE from EDE, and determine the severity of the disease.